Government Strategic Management Through Csr Awards In Realizing The Commitment And Contribution To The Umkm Future In Semarang City - Karjono Karjono; Haryani Haryani; Evyana Diah Kusumawati (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Manufacturing industry activities must be distinct from the role of the surrounding community. For this reason, companies are required to create activities that positively impact the environment and society. The company was founded with specific aims and objectives. Therefore, to achieve this goal, the role of society and the environment is highly expected. One of the government programs that can be implemented to realize the future commitment and contribution of MSMEs is CSR, but giving this award is not only required for profit-oriented business entities. However, it can also be carried out by non-profit-oriented business entities such as universities, which also have responsibilities—social environment. Looking at the factual conditions of giving CSR in the Semarang City CSR application and triggering a breakthrough is needed, including giving a CSR Award. In collecting the data, this research uses a qualitative method, which focusing on data collection and analysis in single studies (single research) and series studies (series assessments). The results of the discussion of this study are to provide input for the Semarang City Government so that CSR awards are given according to applicable rules. They appreciate and motivate companies to distribute CSR programs and synergize government programs with CSR. They are increasing the number of companies joining the Semarang City CSR program. Therefore, giving this CSR award is also a trigger for certain companies to be able to support UMKM products so that they become part of their proud products, too. Keywords. ,, and